"Fistful of Tears": Encounters with Transnational Affect, Chinese Immigrants and Italian Fast Fashion - Krause, Elizabeth L. (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
In the made in italy fast-fashion sector, the ultimate flexible workers are Chinese migrants, whose parenting practices include circulating children back to China. This paper draws on collaborative research in Prato, Italy, to grasp how Chinese families and individuals encounter the Italian state and negotiate the terms of transnational capitalism. The project innovates an encounter ethnography framework to guide research. This paper investigates the dialectic between economics and affect. Chinese immigrants’ desires to make money are situated in three structural encounters, each at a different level of scale: the Wenzhou regional model of economic development; a Central Italian small-firm environment connected to the made in italy brand; and global restructuring of the textile and clothing industry. These encounters structure migrant experiences. Underlying sentiments expose how families cope with the demands of globalization, particularly their work in a sector demanding long hours and a fast production schedule. Adjusting to garment work is expressed as a “fistful of tears”; a decision to circulate children into the care of relatives back home is said to be “the only solution”. This paper uses the concept of “global household” (Safri and Graham 2010) to examine the transnational dispersal of kin networks and migrants’ reliance on the affective circuits of those networks. They illuminate, as Marshall Sahlins (2000) observed, how “capitalist forces are realized in other forms and finalities”, as a result of local cultural practices such mediating global systems.